2015
DOI: 10.1136/gutjnl-2014-309099
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of hepatocellular carcinoma risk prediction scores in a North American patient population with chronic hepatitis B infection

Abstract: Although all models predicted the risk of HCC, models that incorporated parameters of liver function or cirrhosis (CU-HCC/GAG-HCC) were most accurate. Low-risk patients likely require reduced HCC surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 23 publications
4
42
1
Order By: Relevance
“…Other risk scoring systems, such as the GAG-HCC and CU-HCC, consider factors such as presence of cirrhosis and core promoter mutations and may be more accurate, particularly for non-Asian cohorts. 32 HCC risk scoring systems for patients receiving antiviral therapy with adequate viral suppression, and/or in other racial/ethnic groups, including patients from the US and Europe, require further evaluation. 33 …”
Section: Translating Epidemiology Into Risk Stratification In Clinicamentioning
confidence: 99%
“…Other risk scoring systems, such as the GAG-HCC and CU-HCC, consider factors such as presence of cirrhosis and core promoter mutations and may be more accurate, particularly for non-Asian cohorts. 32 HCC risk scoring systems for patients receiving antiviral therapy with adequate viral suppression, and/or in other racial/ethnic groups, including patients from the US and Europe, require further evaluation. 33 …”
Section: Translating Epidemiology Into Risk Stratification In Clinicamentioning
confidence: 99%
“…In Western areas, Asian models were shown to be somewhat less predictive, and those that incorporated parameters of liver function or cirrhosis were the most accurate . However, the small sample size and the heterogeneity of the population chronically infected with HBV combined with the low rates of HCC significantly limited the conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…These models were developed in Asians and the application to other populations is unclear, though one study showed good performance in non-Asians [44] . The platelet, age, gender (PAGE-B score is based on platelet, age and gender and was developed to assess risk of HCC in Caucasians.…”
Section: Limitations Of the Hcc Predictor Modelsmentioning
confidence: 99%